PENYALAHGUNAAN IZIN TINGGAL OLEH WARGA NEGARA INDIA DI INDONESIA: Misuse of Residence Permit by Indian Nationals in Indonesia - Devika Cetirzania; Radian Syam (Faculty of Law, Universitas Trisakti, 2025)
Restrictions on the activities of foreigners in Indonesia are intended to prevent immigration violations, such as misusing visas or residence permits. The misuse of residence permits of two foreign nationals (WNA) from India named Mohammad Zaffer Syed and Syed Naveed violated Law No. 6 of 2011 concerning Immigration by carrying out activities contrary to their limited stay permits. The identification problems of this research are: how the immigration action against the abuse of residence permits by the Indian foreigner is, and whether the immigration action against the two WNAs is in accordance with Law No. 6 of 2011 concerning immigration. The article is a normative legal research, descriptive in nature, using secondary data, then analyzed qualitatively, and the conclusion is drawn deductively. The research and conclusion of this research shows that foreigners from India named Mohammad Zaffer Syed and Syed Naveed Abbas are proven to have misused their residence permit and violated Article 122 letter a of Law No. 6 of 2011 concerning Immigration, and were sentenced to five months imprisonment and a fine of IDR 500,000,000. with the provision that if the fine is not paid, it will be changed to one-month imprisonment.